Entwicklung keramischer Vergussmassen mit Alkoxysilanen zur Steigerung der Haftfestigkeit - Kohler, Tobias (KIT Scientific Publishing, 2023)
The adhesion of encapsulation materials is an dendrimental factor for the robustness and functionality of a power electronic device. In this work the adhesion of ceramic potting materials was developed. A new primer was invented, that enabled high shear strengths even at high temperatures for short times. Furthermore, a completely new potting material was invented on the basis of alkoxysilanes. Especially MTES showed beneficial properties for the adhesion under temperature load.